A sensemaking study of centre-LED change initiatives: The case of a Malaysian based MNE / Nizam Abdullah - Nizam , Abdullah (2018)
The processes or dynamics of micro-political behaviours of centre-led change initiatives are areas of limited research, where far too little is known about the key actors that interact within. This study explores the various patterns of interaction enacted by a centre and subsidiary managers involved in centre-led change initiatives and how they influence the development and outcome of those initiatives. This study’s setting is based on a multi-national enterprise (MNE) headquartered in Kuala Lumpur, Malaysia with several operating subsidiaries in Asia. The MNE is a mobile network operator (MNO) company operating under a single parent branding. In the past few years, the MNE has gone through a series of centre-led change initiatives. Some initiatives resulted in favourable outcomes while others were not. Managers involved in change initiatives, central to this study, serve as the primary unit analysis for this study to be explored. Three key change initiatives identified during a pilot survey were utilized for this exploratory study across four of the MNE subsidiaries. This study contributes to the sensemaking in change literature by illustrating detailed accounts of how the interplay between centre and subsidiary managers determine the outcome of change initiatives. Three sets of sensemaking/sensegiving namely communication intensity, adoption to change and resolution to barriers were identified. Firstly, communication intensity refers to the level of sensemaking and sensegiving enacted by managers throughout the development of change. Secondly, adoption to change refers to the level of change, this ranges from minimal adopters to active adopters (Kostova & Roth, 2002). Finally, resolution to barriers refers to the efforts taken to overcome barriers to change initiative. The subsidiary that adopts the most centre-led initiatives displays intense sensemaking by managers at both the centre-subsidiary and subsidiary level. The subsidiary that goes beyond adoption and into the realm of adaptation, high level of organisational sensemaking and sensegiving were happening at the same time. For these subsidiaries, sensemaking and sensegiving was active even at the subsidiary-to-subsidiary manager level. At the subsidiary-to-subsidiary manager level, a plot by a certain group of subsidiaries was unveiled to counter the centre’s influence. In the space for practitioners, centre managers should consider stronger and deeper sensegiving throughout the development initiatives stage. Any confusion, distraction or uncertainty needs to be addressed swiftly and firmly by the centre managers. This study suggests that the centre-led initiatives' outcome mostly depends on the centre managers’ role and guidance throughout the initiatives’ critical development stage. Finally, this multiple embedded case study performed at a mobile network operator MNE suggests that early subsidiary's involvement is the key in ensuring a strong buy-in throughout the development stage of the change initiative.